(untitled) (Experimental biology, 2009)
The statistical study 200 women are organized in program IVF, is given estimation their reproductive abilities. The half of these women was chose as checking group in which was not a breach of the menstrual cycle, but beside the second half were, a different breaches of the menstrual cycle. From 100 women with menstrual frustration, excess of the mass of the body existed beside 47 more than 25%. In checking group of the women with normal menstrual cycle frequency appearance obesities was only 14%. On total called on statistical analysis was revealled, relationship between 101 obesity and breaches of the menstrual cycle, in the manner of positive correlation. Beside 44% women with android type of the obesity existed, the different breaches to functions gonad.